CMTM6 shapes antitumor T cell response through modulating protein expression of CD58 and PD-L1 - Miao, Beiping; Hu, Zhaoqing; Mezzadra, Riccardo; Hoeijmakers, Lotte; Fauster, Astrid; Du, Shangce; Yang, Zhi; Sator-Schmitt, Melanie; Engel, Helena; Li, Xueshen; Broderick, Caroline; Jin, Guangzhi; et al. (Cancer cell, 2023)
The dysregulated expression of immune checkpoint molecules enables cancer cells to evade immune destruction. While blockade of inhibitory immune checkpoints like PD-L1 forms the basis of current cancer immunotherapies, a deficiency in costimulatory signals can render these therapies futile. CD58, a costimulatory ligand, plays a crucial role in antitumor immune responses, but the mechanisms controlling its expression remain unclear. Using two systematic approaches, we reveal that CMTM6 positively regulates CD58 expression. Notably, CMTM6 interacts with both CD58 and PD-L1, maintaining the expression of these two immune checkpoint ligands with opposing functions. Functionally, the presence of CMTM6 and CD58 on tumor cells significantly affects T cell-tumor interactions and response to PD-L1−PD-1 blockade. Collectively, these findings provide fundamental insights into CD58 regulation, uncover a shared regulator of stimulatory and inhibitory immune checkpoints, and highlight the importance of tumor-intrinsic CMTM6 and CD58 expression in antitumor immune responses.
Gesehen am 08.07.2024